Negosiasi Identitas Perempuan Bercadar dalam Menghadapi Stigma Attached To Identification selama Proses Pembelajaran - Najla Assyifa Asayanda Gunawan; Hapsari Dwiningtyas Sulistyani; Muchamad Yuliyanto (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
The use of the veil in the midst of a pluralistic Indonesian society reaps various views, including stigma, even though a person has the right to have the freedom to show their identity through clothing. This situation makes veiled women not fully accepted so they need to negotiate their identities, including in the realm of education at the university level. This study aims to understand the experiences of veiled women negotiating their identities in the face of stigma and different views regarding the veil during learning. This study uses the Interpretative Phenomenological Analysis (IPA) method with in-depth interviews. The results of the study illustrate that the three informants interpret the veil in relation to religious beliefs that form their self-concept and social identity, namely the three informants see themselves as continuing to maintain attitudes and behavior to conform to their veiled identity. Furthermore, the three informants entered a diverse lecture environment and interacted with friends and lecturers during the learning process. In this case, the three informants faced various differences, including differences in views and the stigma of the veil so that the three informants negotiated to communicate their identities. Based on relation and situation factors, several strategies were found in the negotiating process of the three informants, including avoiding, compromising, competing, accommodating, and collaborating. Through various strategies, the three informants were able to communicate their identities so that they were understood and good relations were established.